Effect of resistance training on body composition and physical function in older females with sarcopenic obesity—a systematic review and meta-analysis of randomized controlled trials - Guo, Changsheng; Dai, Ting; Zhang, Haoran; Luo, Meng; Gao, Jing; Feng, Xiaodong (Frontiers in Aging Neuroscience, 2025)
ObjectivesA systematic review and meta-analysis was conducted to validate the effects of resistance training (RT) on body composition and physical function in older females with sarcopenic obesity (SO).DesignSystematic review and meta-analysis.Setting and participantsOlder females (≥60 years).MethodsFour electronic databases—PubMed, Web of Science, Embase, and the Cochrane Library—were comprehensively searched through June 2024. Randomized controlled trials (RCTs) comparing RT with non-exercise interventions or health education were included. Outcomes measured included key indicators such as body composition and physical function. The quality of the included studies was evaluated using the Physiotherapy Evidence Database (PEDRO) score, and the risk of bias was assessed utilizing the Cochrane Risk of Bias 2.0 Tool (RoB 2). Ultimately, a meta-analysis was conducted using RevMan 5.4.ResultsResults of our meta-analysis revealed that RT partially ameliorated body composition in patients, significantly reducing body fat percentage (BF%; WMD = −2.83, 95% CI: −4.55 to −1.12, p = 0.001). However, through comparative analysis of the control groups, we revealed that it did not significantly influence other indices such as body mass index (BMI; WMD = −0.42, 95% CI: −1.92 to 1.08, p = 0.58), total skeletal muscle mass (TSM; WMD = −0.62, 95% CI: −2.38 to 1.15, p = 0.49), or bone mineral density (BMD; WMD = 0.01, 95% CI: −0.03 to 0.05, p = 0.68). Notably, RT demonstrated substantial efficacy in enhancing physical function, as evidenced by improvements in the 10-meter walk test (10WMT; WMD = 0.22 s, 95% CI: 0.04 to 0.39, p = 0.01), Timed Up and Go test (TUG; WMD = −2.23 s, 95% CI: −2.96 to −1.49, p = 0.00001), and Timed Chair Rise test (TCR; WMD = 5.20 repetitions, 95% CI: 3.98 to 6.43, p = 0.00001).ConclusionThis meta-analysis indicates that RT exerts a significant positive influence on the physical function of older females with SO. Despite these benefits, the impact on body composition parameters, such as BF%, appears to be limited. These findings underscore the need for further investigation into the mechanisms by which RT affects body composition in this patient population.Systematic review registrationINPLASY202430061 https://inplasy.com/inplasy-2024-3-0061/.